2015
DOI: 10.5051/jpis.2015.45.3.120
|View full text |Cite
|
Sign up to set email alerts
|

Microgrooves on titanium surface affect peri-implant cell adhesion and soft tissue sealing; an in vitro and in vivo study

Abstract: PurposeWith the significance of stable adhesion of alveolar bone and peri-implant soft tissue on the surface of titanium for successful dental implantation procedure, the purpose of this study was to apply microgrooves on the titanium surface and investigate their effects on peri-implant cells and tissues.MethodsThree types of commercially pure titanium discs were prepared; machined-surface discs (A), sandblasted, large-grit, acid-etched (SLA)-treated discs (B), SLA and microgroove-formed discs (C). After surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 15 publications
2
33
0
1
Order By: Relevance
“…Peri-implant soft tissue is vulnerable to bacterial invasion that may cause peri-implant disease [1]; therefore, the key to the success of dental implantation is the constitution of a soft tissue barrier able to promote osseointegration surrounding the implant body [2]. Learning how to form firm and functional soft tissue sealing around the titanium implant is particularly important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peri-implant soft tissue is vulnerable to bacterial invasion that may cause peri-implant disease [1]; therefore, the key to the success of dental implantation is the constitution of a soft tissue barrier able to promote osseointegration surrounding the implant body [2]. Learning how to form firm and functional soft tissue sealing around the titanium implant is particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the micro-grooved structure effectively induced the formation of the vertical direction of the collagen fiber secreted by cells, guided the cell alignment and elongation along the microgroove, limited the epithelial cell downward growth, and decreased the occurrence of inflammation around implants [4,5]. Compared with smoothed titanium, micro-grooved titanium substrata promoted the adhesion and proliferation of HGFs as well as adhesion to peri-implant soft tissue [1,6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…6(a-d), and the measured roughness values are listed in [50][51][52] assessed the favorable outcome of rough surface acquired by surface treated practice on osseointegration process. In general, the surface roughness of the polymer coating is a signicant feature that can obviously inuence its corrosion protection behavior and further properties, including hydrophobicity, appearance and bioactivity in physiological environments.…”
Section: Surface Characterization Of Pedot Lms Synthesized On Treatementioning
confidence: 99%
“…Surface roughness is also one of the key factors in implant design. Many studies have investigated the effect of implant surface roughness on marginal bone loss, and others have evaluated optimal roughness to prevent marginal bone loss, but the topic is still controversial …”
mentioning
confidence: 99%
“…Many studies have investigated the effect of implant surface roughness on marginal bone loss, and others have evaluated optimal roughness to prevent marginal bone loss, but the topic is still controversial. [22][23][24][25] Clinically, implant fixtures are not always fully submerged into alveolar bone, leaving threads exposed during implant placement because of poor technique or a less experienced operator. This situation can be found especially during a flapless approach.…”
mentioning
confidence: 99%